## Simplifying Expressions with Substitution

This article explores how to simplify an expression by substituting a specific value for a variable.

Let's consider the expression **(b - 7)² - b² + 7** and determine its value when **b = -13/14**.

### Step 1: Substitute the value of 'b'

Replace each instance of 'b' in the expression with the given value, -13/14:

**( -13/14 - 7 )² - ( -13/14 )² + 7**

### Step 2: Simplify the expression

Follow the order of operations (PEMDAS/BODMAS) to simplify the expression:

**Parentheses/Brackets:**-13/14 - 7 = -111/14**Exponents/Orders:**(-111/14)² = 12321/196 and (-13/14)² = 169/196**Multiplication and Division:**(No operations in this step)**Addition and Subtraction:**12321/196 - 169/196 + 7 = 12152/196 + 7 = 12850/196

### Step 3: Simplify the result (optional)

The result can be simplified further by dividing both numerator and denominator by their greatest common factor, which is 2:

12850/196 = **6425/98**

Therefore, the value of the expression **(b - 7)² - b² + 7** when **b = -13/14** is **6425/98**.